The role of prototype fidelity in technology crowdfunding - Wessel, Michael; Thies, Ferdinand; Benlian, Alexander (Journal of Business Venturing, 2022)
The presentation of a prototype is pervasive when technology entrepreneurs pitch to potential resource providers. Yet, we know little about how the fidelity of a prototype—the degree to which it approximates the final product—can affect funding decisions. We study the relationship between prototype fidelity and resource acquisition of nascent technology ventures in online crowdfunding. Based on the community logic under which crowdfunding operates and the diverse motivations of funders to participate, we develop the seemingly counterintuitive idea that moderate prototype fidelity is more effective in gaining support from funders than high prototype fidelity. Across our three empirical studies, we find support for the hypothesis that prototype fidelity has an inverted U-shaped relationship with crowdfunding performance. This relationship is moderated by the materiality of the offered rewards and the quality of the prototype presentation delivered through the online interface.